Detection of Radio Frequency Interference in Satellite Ground Segments - Coppolino, Luigi; D'Antonio, Salvatore; Uccello, Federica; Lyratzis, Anastasios; Bakalis, Constantinos; Touloumtzi, Souzana; Papoutsis, Ioannis (2023 IEEE International Conference on Cyber Security and Resilience (CSR), 2023)
The Copernicus era in Europe has resulted in an increase in the processing of satellite data, making the space sector an attractive target for cyber-attacks. RF attacks can potentially disrupt the management and distribution of satellite data and pose a significant risk to public safety and national security. The 7SHIELD project aims to develop a comprehensive framework for the protection of ground segments of space systems, which includes innovative services such as e-fences, passive radars, and laser technologies. Among the key modules developed within the project, the Cyber-Attack Detection Framework (CADF) has been developed to provide real-time correlation and detailed alerts in case anomalies are detected, providing support to the modules in charge of mitigation strategy. The CADF has been successfully tested against RF jamming attacks along with the rest of the 7SHIELD framework within an actual Critical Infrastructure, the Satellite Ground Station in Penteli, Athens, Greece.